Uma experiência de formação docente em Língua Portuguesa no contexto do Pibid - Eles, Rejane Maria Oliveira (2014)
Teacher training has been the focus of investigative research of qualitative nature. In the context of this investigation, we considered the studies performed by Schön (2000) on reflexive-professor as focus for teacher formation issues, the dialogicity defended by Freire (1996), as well as the teaching knowledge of Tardif (2012), which permeate the life of a teacher in formation, in order to attempt at describing the formation process of a Portuguese Language (PL) teacher. Therefore, in this study, the general objective was to observe and describe the formation process of teachers by means of teaching practices for PL in the context of PIBID. The specific objectives were to describe, analytically, the pedagogical practices in order to categorize them according to the moments of reflection exposed in the daily dialog journals of pre-service teachers. The methodology is configured as a qualitative approach, based on the empirical knowledge for epistemological curiosity, that is, a case study, given that it derives from the livelihood of the teacher-supervisor-researcher in the context of PIBID. The analysis was conducted after the interpretation of the reflexive-dialog journals in order to understand the teacher formation processes. The results showed that, although, if there was an outlining of how to teach the content of Portuguese Language from theories of language interaction, there were many drawbacks for performing the pedagogical proposals regarding this conception. We also verified that, by means of the speech in the reflexive-dialog journals, and comparing these them before and after applying the activities, the progression of the reflection in the practices executed, made possible by the situations of anguish, questionings and self-assessment of our teaching practice.